SARS-CoV-2 infection provoking autoimmunity - Mahroum, Naim; Shoenfeld, Yehuda (Oxford University Press, 2023)
For decades, infections have been recognized as strong stimulators of the immune system and subsequently serve as a trigger for autoimmunity and autoimmune diseases. While infection is a very broad term, infectious agents such as bacteria, viruses and parasites, but particularly viruses present a key player in this regard and have been considered a classical example for this correlation.
Keywords: Autoimmunity; Infection; SARS-CoV-2